Biological standards of living: age at menarche vs height. (2nd January 2017) - Sohn, Kitae
Abstract: Background Researchers typically use height to understand the growth environment, but recent evidence suggests that height does not reflect it well; height can even be misleading. Aim This study compared age at menarche and height to assess which better reflected the growth environment. Subjects and methods This study employed the Indonesian Family Life Survey to extract information on age at menarche from 7831 women and height from 7946 men, both aged 15–49 and born in 1944–1983. It drew on GDP per capita in childhood to represent the growth environment. The means of the two anthropometrics by birth decade were calculated. The trends in the two were then compared and each was regressed on the growth environment and a time trend. Results Between 1944–1953 and 1974–1983, the mean age at menarche decreased from 14.5 to 13.9, while height increased from 160.9 cm to 162.6 cm. Despite the expected broad trends, age at menarche was more closely related to the growth environment than height in graphs, correlation coefficients and regression results. Conclusion The results recommend using more than one anthropometric to investigate changes in the biological standards of living.